Spontaneous Coronary Artery Dissection of the Left Main Coronary Artery - Suresh, Avanti (Cureus, 2020)
Heart attacks in young populations are frequently misdiagnosed as reflux disease or anxiety. Spontaneous coronary artery dissection (SCAD) is a coronary artery disease that classically manifests around the age of 45 years and has a fatal outcome if missed. Since it was first described in 1931, our understanding of SCAD has evolved tremendously, particularly with the advent of advanced coronary angiography. Electrocardiograms can show abnormality in the ST-segment, with an elevation of cardiac damage markers. The involvement of the coronary arteries is variable. The left main coronary artery is frequently reported as the main culprit. We are hereby reporting a case of SCAD in a young woman who presented with a heart attack. Particularly, her age is younger than the reported cases, cardiac catheterization revealed a left main artery dissection with a thrombolytic extension, and her complicated case was managed with coronary artery bypass and heart transplantation.